A Comparison of Analysts' and Investors' Biases in Interpreting Accruals: A Valuation Approach - Yoo, Yong Keun (Institutional Knowledge at Singapore Management University, 2007)
Elgers, Lo, and Pfeiffer (2003) argue that analysts' earnings forecasts are less biased than the market's earnings expectation in interpreting accruals. Their argument implies that analysts' earnings forecasts could potentially mitigate the market's mispricing of accruals by guiding investors to reduce their earnings prediction errors arising from the misinterpretation of accruals. Their results call for further investigation, however, owing to two questionable research design choices: (1) estimating the magnitude of the market's bias using the traditional earnings response coefficient (ERC) model, which is vulnerable to the well-known omitted-variable problem; and (2) examining only the bias in short-term (i.e., one-year-ahead) earnings expectations, ignoring possible bias in earnings expectations for longer future periods. To alleviate these concerns, we take an alternative approach in which we compare the bias of the market's equity value estimates (i.e., stock prices) against the bias of equity value estimates based on analysts' earnings forecasts in valuing accruals. By taking this alternative approach, we find that analysts' earnings forecasts are more biased than stock prices in interpreting accruals. Thus, contrary to Elgers, Lo, and Pfeiffer (2003), we conclude that analysts' earnings forecasts do not mitigate the market's mispricing of accruals. [ABSTRACT FROM AUTHOR]